2011
DOI: 10.3343/kjlm.2011.31.2.72
|View full text |Cite
|
Sign up to set email alerts
|

New Biomarkers of Acute Kidney Injury and the Cardio-renal Syndrome

Abstract: Changes in renal function are one of the most common manifestations of severe illness. There is a clinical need to intervene early with proven treatments in patients with potentially deleterious changes in renal function. Unfortunately progress has been hindered by poor definitions of renal dysfunction and a lack of early biomarkers of renal injury. In recent years, the definitional problem has been addressed with the establishment of a new well-defined diagnostic entity, acute kidney injury (AKI), which encom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 97 publications
0
43
0
8
Order By: Relevance
“…In previous studies, NGAL was effective in the early diagnosis of acute kidney injury (AKI) in several clinical settings 25 and was also validated for its prognostic role in cardiovascular morbidity. 26,27 Cystatin C (CysC) is a small-molecular-weight protein and, in particular, an endogenous cysteine proteinase inhibitor highly correlated with GFR. 28 It is not influenced by inflammatory conditions, muscle mass, gender, body composition and age (after the age of 12 months).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, NGAL was effective in the early diagnosis of acute kidney injury (AKI) in several clinical settings 25 and was also validated for its prognostic role in cardiovascular morbidity. 26,27 Cystatin C (CysC) is a small-molecular-weight protein and, in particular, an endogenous cysteine proteinase inhibitor highly correlated with GFR. 28 It is not influenced by inflammatory conditions, muscle mass, gender, body composition and age (after the age of 12 months).…”
Section: Introductionmentioning
confidence: 99%
“…50,51 In some recent studies serum level of NGAL was found to be increased at the end of second trimester in women who subsequently developed PE compared to control group. 47,49,52 A positive correlation of serum NGAL was found with the systolic and diastolic blood pressure and with proteinuria. 38,47,49 Hence serum NGAL can be used as a reliable biomarker for early prediction of pre-eclampsia.…”
Section: Neutrophil Gelatinase-associated Lipocalin (Ngal)mentioning
confidence: 87%
“…48,49 It is also known as lipocalin-2, siderocalin, uterocalin and 24p3. 48,49 It was fi rst identifi ed as a matrix protein of specifi c granules of human neutrophils. Its expression is highly upregulated in damaged epithelial cells, during infl ammation, neoplastic conditions, cardiovascular diseases, infections and renal disorders.…”
Section: Neutrophil Gelatinase-associated Lipocalin (Ngal)mentioning
confidence: 99%
“…There is a need for new specific biomarkers that identify kidney injury early and that can replace serum creatinine in both the definition of AKI for epidemiological and study purposes as well as in guiding individual patient management [5].…”
Section: -Fasting Plasma Glucose Level By Colorimetric Methodsmentioning
confidence: 99%
“…In AKI, serum creatinine elevation that reflects the development and severity of kidney damage does not occur until days after renal tubular injury has begun [4]; thus, there is a need for new specific biomarkers that identify kidney injury early and that can replace serum creatinine in both the definition of AKI for epidemiological and study purposes as well as in guiding individual patient management [5] Fatty acid binding proteins are small (15 kDa) cytoplasmatic proteins abundantly expressed in tissues with active fatty acid metabolism [6]. The liver type fatty acid binding protein is a newly emerging biomarker that has antioxidant properties, and enhanced expression in proximal tubule cells and subsequent urinary excretion are known to reflect the presence of tubular injury [7].…”
Section: Introductionmentioning
confidence: 99%